Editor's Choice – Prevalence of Peripheral Arterial Disease, Abdominal Aortic Aneurysm, and Risk Factors in the Hamburg City Health Study: A Cross Sectional Analysis. (April 2023) - Behrendt, Christian-Alexander; Thomalla, Götz; Rimmele, David L.; Petersen, Elina L.; Twerenbold, Raphael; Debus, Eike S.; Kölbel, Tilo; Blankenberg, Stefan; Schmidt-Lauber, Christian; Peters, Frederik; Zyriax, Birgit-Christiane
Abstract : Objective: There is a paucity of current figures on the prevalence of carotid and lower extremity peripheral arterial disease (PAD) and abdominal aortic aneurysm (AAA) as well as the associated cardiovascular risk factors to support considerations on screening programmes. Methods: In the population based Hamburg City Health Study, participants between 45 and 74 years were randomly recruited. In the current cross sectional analysis of the first 10 000 participants enrolled between February 2016 and November 2018, the prevalence of carotid artery disease (intima–media thickness ≥ 1 mm), lower extremity PAD (ankle brachial index ≤ 0.9), and AAA (aortic diameter ≥ 30 mm) was determined. Multivariable logistic regression models were applied to determine the association between vascular diseases and risk factors. To account for missing values, multiple imputation was performed. Results: A total of 10 000 participants were analysed (51.1% females, median age 63 years, median body mass index 26.1 kg/m 2 ). In medians, the intima media thickness was 0.74 mm (interquartile range [IQR] 0.65 – 0.84), the ankle brachial index 1.04 (IQR 0.95 – 1.13), and the aortic diameter 17.8 mm (IQR 16.1 – 19.6). Concerning risk factors, 64% self reported any smoking, 39% hypertension, 5% coronary artery disease, 3% congestive heart failure, 5% atrial fibrillation, and 3% history of stroke or myocardial infarction, respectively. In males, the prevalence of carotid artery disease, lower extremity PAD, and AAA were 35.3%, 22.7%, and 1.3%, respectively, and in females, 23.4%, 24.8%, and 0.2%, respectively. Higher age and current smoking were likewise associated with higher prevalence while the impact of variables varied widely. Conclusion: In this large population based cohort study of 10 000 subjects from Hamburg, Germany, a strikingly high prevalence of PAD was revealed. Almost 45% suffered from any index disease, while AAA was only diagnosed in 1.3% of males and 0.2% of females. The high prevalence of atherosclerotic disease and associated cardiovascular risk factors underline that it is essential to increase awareness and fuel efforts for secondary prevention.